Retinal Degeneration: A Window to Understand the Origin and Progression of Parkinson’s Disease? - Zhang, Yanyan; Zhang, Xiaoguang; Yue, Yunhua; Tian, Tian (Frontiers in Neuroscience, 2022)
Parkinson’s disease (PD), the second most prevalent neurodegenerative disorder, manifests with motor and non-motor symptoms associated with two main pathological hallmarks, including the deterioration of dopaminergic cells and aggregation of alpha-synuclein. Yet, there are so far no established diagnosis marks and therapeutic interventions to timely prevent the occurrence and development of PD owing to its unclear aetiology. Currently, retinal imaging technology detects neuropathological changes and can provide a growing body of information about the structure and function of retinal tissue. Since the retina has similar neuroanatomical basis and functional relevance to the brain, retinal technologies such as optical coherence tomography may provide a promising noninvasive means to understand, diagnose and monitor the neurological disease. Remarkably, research on retinal morphological and function abnormality has grown in recent years with the increasing development of high spatial resolution and low-cost of retinal imaging modalities and usage of biomarkers in clinical research of PD. In this review, we first provide an overview of the basic physiology of visual function and retinal structure to understand the structure-function relationship in retina. Then, we summarize recent advances in retinal imaging techniques that have improved our understanding of retinal function and tissue architecture. On the basis of the current status of numerous visual deficits in individuals with PD, we also discuss the modalities and pathological mechanism of visual function or retina-related morphological changes in patients with PD, and focus on the correlation between visual impairment and some representative structural features with clinical significance. Furthermore, we highlight retinal morphological changes in the diagnosis and effective therapeutic perspectives of PD. To integrally evaluate molecular disorders, functional and structural changes in the retina is significant for the early diagnosis and therapeutic strategies of neurodegenerative diseases.